Knowledge Platform for Inclusive and Sustainable Food Markets and Value Chains: IPSR Innovation Profile - Vos, Rob; Kim, Soonho; Rangan, V.; Dimaranan, Betina (CGIAR System Organization, 2024)
Knowledge Platform to facilitate evidence-based decision-making of governments, businesses, farmers, and practitioners toward more Inclusive and Sustainable Food Markets and Value Chains (KISM). The platform consolidates evidence of existing experiences with product and process innovations within food value chains regarding their inclusiveness (employment and income generation, valueadded sharing, poverty reduction, food security) and sustainability (emissions, supply chain resilience).